Meningkatkan Peran Generasi Muda dalam Mendukung Green Economy dengan Instrumen Investasi Berbasis Environmental, Social, and Governance (ESG) melalui Program Dimension Circular - Ilham Febri Budiman; Michael Boris Rasi Sitanggang; Muhammad Rafly Hidayat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In recent years, the issue that has become a hot topic of discussion among both the national and international communities is the issue of environmental damage. Therefore, in the economic context, there is a need for a transformation towards a green economy. The Indonesian government is promoting the TPB/SDGs Indonesia 2030 program. Realizing the Sustainable Development Goals (SDGs) 2030 is a shared responsibility that requires participation from all sectors, including the government, civil society, and the private sector. Therefore, considering the importance of sustainable development in the field of investment itself, several global organizations have established a measure that calculates sustainable development known as ESG investing. ESG consists of Environment, Social, and Governance, which adds value to companies that care about and think about the environment, such as issues related to carbon emissions, water and air pollution, and other environmental issues. This research aims to determine the role of the younger generation as agents of change through ESG Investment in realizing the 2030 SDGs. The research method utilized in this scientific paper is a combination research method with data collection through literature review. This research is expected to provide insights into the urgency of the younger generation in realizing the 2030 SDGs.